Consumer's choice and decision making of mobile phone service operator - Khairuddin, Siti Khairulnur Azlinda (2001)
Previosly, the Malaysian telecommunication industry was monopolised by Telekom Malaysia Berhad, but now with four other main players in the field, consumers are at the advantage of having loathed of choices. Basically the objective of this study is to determine factors that consumers take into consideration when they evaluate among the choices before deciding which of the mobile phone service operators that they will subscribe to. The study was conducted in Klang Valley area. The convenience sampling technique was utilised in identifying the sample, which consists of 200 respondents that owned a mobile phone. Data for the study were collected through personal interview via structured questionnaire. The data were analysed using t-test and analysis of variance. From the three factors of service quality, price and brand image beng examined in this study, it was found that service quality has the most influence on consumer's choice of mobile phone service operators, mainly on the wide coverage area provided coupled with good transmission and receptions, followed by price and brand image that was considered as not so important in the consumer's point of view. Thus, mobile phone service operators should revise the quality of the service that they are currently providing their customers with, as this might be the means to increase their subscriber base.